Update on pharmacist role in sterile compounding in hospital - Albesht, Hanan; Hanifah, Suci; Abukres, Salem (Jurnal Ilmiah Farmasi, 2025)
Background: Sterile compounding, a critical aspect of pharmaceutical practice, involves the preparation of customized medications in a sterile environment. Pharmacists play a pivotal role in ensuring the safety and efficacy of compounded sterile products (CSPs), making their involvement integral to the healthcare system. Objective: This article aims to describe the role of pharmacists in sterile compounding based on literature. Method: Articles from Medline/PubMed, guidelines, reports, and databases related to sterile compounding have been searched and compiled. This review collected the qualitative data and identified the critical point for continuous quality improvement initiatives in sterile compounding.Results: This comprehensive narrative review explores the multifaceted responsibilities of pharmacists in sterile compounding, drawing insights from various studies and databases. However, the study related to the pharmacist's role in sterile compounding practices is very limited. Recent articles that mention the pharmacist's role in sterile compounding commonly come from the guidelines or government documents. In general, CSP needs a commitment to comply with regulatory standards for achieving patient safety using the integration of technology and healthcare collaboration. Continuous professional development is a crucial contributor to keeping the quality of compounded sterile products. Conclusion: The findings from various journals underscore the complexity of their responsibilities and emphasize the need for a holistic approach to ensure the integrity and safety of compounded sterile products in diverse healthcare settings.